Subcutaneous phaeohyphomycosis from Medicopsis romeroi in a diabetic patient - Pattriya Chanyachailert (2020)
© 2019 The Authors Dematiaceous fungi can cause subcutaneous phaeohyphomycosis, an uncommon fungal infection of the dermis and subcutaneous tissues. Medicopsis romeroi is an emerging organism that can infect patients with subcutaneous phaeohyphomycosis, especially immunocompromised patients. The present case involved subcutaneous phaeohyphomycosis caused by Medicopsis romeroi in an 80-year-old Thai male with poorly controlled diabetes, for whom the lesion underwent spontaneous remission after his glycemic control was improved. Furthermore, cases of subcutaneous phaeohyphomycosis for the last 10 years were reviewed.